Herpes zoster is associated with herpes simplex and other infections in under 60 year-olds. Issue 2 (February 2015) - Ogunjimi, Benson; Buntinx, Frank; Bartholomeeusen, Stephaan; Terpstra, Ita; De haes, Inke; Willem, Lander; Elli, Steven; Bilcke, Joke; Van Damme, Pierre; Coenen, Samuel; Beutels, Philippe
Summary Objectives We assessed the association between herpes zoster (HZ) and herpes simplex (HS) occurrence whilst controlling for risk factors of HZ. Methods Using a Belgian general practitioner network, a retrospective cohort study with 3736 HZ patients and 14, 076 age-gender-practice matched controls was performed, covering over 1.5 million patient-years. Multiple logistic regression was used with HZ as outcome and several diagnoses (malignancy, depression, diabetes mellitus, auto-immune diseases, asthma, multiple sclerosis, HIV, fractures), medications (systemic corticosteroids, biologicals, vaccination), HS and other infections as variables. Results HS was significantly associated with HZ for all analysed time intervals (up to five years) post HZ (OR of 3.51 [2.09 5.88] 95%CI one year post HZ) and to a lesser extent for time ranges pre HZ. Registration of other infections was significantly associated with HZ in all time intervals pre and post HZ (OR up to 1.37). Malignancy up to five years pre HZ, depression up to one year pre or post HZ, fractures up to two years pre HZ, asthma, auto-immune diseases, and immunosuppressive medication one year pre or post HZ were also associated with HZ. Conclusions HZ and HS occurrences are significantly associated and potentially share a common susceptibility beyond the known risk factors.